The Practice of Physical Medicine and Rehabilitation in subSaharan Africa and Antarctica: A White Paper or a Black Mark? - Haig, Andrew J.; Im, Jonathan; Adewole, Ayodeji; Nelson, Virgina S.; Krabak, Brian (PM&R, 2009)
Peer Reviewed https://deepblue.lib.umich.edu/bitstream/2027.42/147120/1/pmr2421.pdf